2020
DOI: 10.1038/s41598-020-71637-z
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the spectral collapse in two-photon Rabi model

Abstract: We have investigated the eigenenergy spectrum of the two-photon Rabi model at the critical coupling, particularly the special feature “spectral collapse”, by means of an elementary quantum mechanics approach. The eigenenergy spectrum is found to consist of both a set of discrete energy levels and a continuous energy spectrum. Each of these eigenenergies has a two-fold degeneracy corresponding to the spin degree of freedom. The discrete eigenenergy spectrum has a one-to-one mapping with that of a particle in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…This is in sharp constrast to the findings reported in Ref. 24 , which explicitly shows that the discrete eigenenergy spectrum has a one-to-one mapping with that of a particle in a "Lorentzian function" potential well, and that each eigenenergy is doubly degenerate. Particularly, Ref.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This is in sharp constrast to the findings reported in Ref. 24 , which explicitly shows that the discrete eigenenergy spectrum has a one-to-one mapping with that of a particle in a "Lorentzian function" potential well, and that each eigenenergy is doubly degenerate. Particularly, Ref.…”
Section: Resultssupporting
confidence: 83%
“…All in all, similar to Ref. 24 , the present work is capable of providing a clear and concise treatment of the incomplete spectral collapse of the multi-qubit two-photon Rabi model at the critical coupling.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…e . 12 24 . That is, as the coupling strength increases, the spacing of the discrete eigenenergy levels of the two-photon Rabi model diminishes monotonically, leading to a continuum energy spectrum beyond the critical value.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic behaviour of the eigenstates at the critical coupling thus remains as a mystery until recently. Lo 24 has rigorously shown that at the critical coupling some discrete energy levels exist below a continuum energy spectrum, and the number of these bound states available depends upon the energy difference between the two atomic levels. In other words, incomplete spectral collapse appears at the critical coupling.…”
Section: Introductionmentioning
confidence: 99%